Examining the Relationship between Emotional Intelligence, Achievement Motivation, and Self-Efficacy among Pre-Service Teachers in Türkiye - Umran Atik; Mehmet Akif Karaman; Halil Ibrahim Sari (MDPI AG, 2024)
The main goal of this study was to examine the extent to which the demographic characteristics of pre-service teachers (gender, family management style, family educational status, size of the family) predict their emotional intelligence (EI) scores through achievement motivation (AMO) and Self-Efficacy (SE) scores. The study consisted of 326 pre-service teachers (270 females, 56 males) studying in various departments at faculties of education across three universities located in the Eastern and Southeastern Anatolia regions of Turkiye. The findings indicate that the demographic variables (gender, family management style, family size, family educational status) do not significantly explain the EI levels of pre-service teachers. A moderately positive relationship was found between AMO and EI, but it was observed that AMO is not a significant predictor of EI. A high positive relationship was detected between SE and EI; it was observed that SE explained 63% of the variance in EI. We found that there was no significant difference between the AMO, SE, and EI scores of pre-service teachers studying at different grade/class levels. As we continue to investigate these topics, it becomes evident that teacher education may continue promoting not only cognitive development but also emotional and social development.